Glutaraldehyde in dentistry--a review - Rusmah, M. (1993)
The disinfective and fixative properties of glutaraldehyde are now widely investigated. Glutaraldehyde is effective against micro-organisms and their spores. Recently, studies have shown the effectiveness of glutaraldehyde against the HIV virus. 2% glutaraldehyde is now recommended for the sterilisation of surgical instruments, operating areas, dental impressions and root canals during endodontic therapy. Studies have also shown that glutaraldehyde is an effective fixative with minimum side effects, limited penetration and quick acting. Pulpotomy studies using glutaraldehyde as the fixative agent produce high success rates. The important feature is the vital pulpal tissue at the apical third suggesting its limited penetration. The small amounts that get distributed systemically are quickly metabolised and excreted in the urine or exhaled as carbon dioxide.